1999
DOI: 10.1007/s11325-999-0047-y
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea in Moderate-Severe Obese Patients

Abstract: Obesity induces multiple physiologic changes at the respiratory and circulatory systems level. A study was developed to identify symptoms and signs able to discriminate subjects at high risk of obstructive sleep apnea (OSA) and to evaluate the presence of OSA in a population of obese patients referred to the Clinical Nutrition Service of the Luigi Sacco Hospital for weight loss therapy. Twenty-seven obese patients (14 males, 13 females) without neurologic, cardiac, and lung diseases were measured for height, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
3
2
0
2
Order By: Relevance
“…[2024] The present study has also shown similar findings and strikingly the minimal oxygen saturation was well below 90% in both the groups. The etiology of OSA in obese has been linked with anatomic alterations that predisposes to upper airway obstruction during sleep.…”
Section: Discussionsupporting
confidence: 87%
“…[2024] The present study has also shown similar findings and strikingly the minimal oxygen saturation was well below 90% in both the groups. The etiology of OSA in obese has been linked with anatomic alterations that predisposes to upper airway obstruction during sleep.…”
Section: Discussionsupporting
confidence: 87%
“…This analysis showed increased deposition of adipose tissue in central regions in morbidly obese individuals with OSA as compared with those without this respiratory disorder. Our results are consistent with other reports in the general population that central adiposity is associated with an increased likelihood of developing sleep apnoea 9–11 . However, our data are unique and show that even among the morbidly obese (BMI >40 kg/m 2 ), these patterns remain.…”
Section: Discussionsupporting
confidence: 93%
“…T. Young и со ав то ры (1993) по ка за ли, что уве ли че ние ИМТ на од но стан дарт ное от кло не ние при во дит к че ты рёх крат но му уве ли че нию ри с ка по па да ния в груп пу боль ных СО АС [35]. Сре ди боль ных ожи ре ни ем пред став лен ность СО АС зна читель но вы ше, чем в це лом в по пу ля ции -55%, по данным M. Sergi и со ав то ров (1999) [26].…”
Section: мг полуэктовunclassified
“…R. Grunstein и со ав то ры до ка зы ва ют, что аб до ми наль ный тип ожи ре ния пред рас по ла га ет к разви тию об ст рук тив ных ап ноэ во сне, при чем он яв ля ется не за ви си мым фак то ром уве ли че ния чис ла ды хатель ных рас ст ройств [12]. D. Revicki и R. Israel (1986) для пре дик ции зна че ний ИДР под чёр ки ва ют важность та ко го по ка за те ля, как ок руж ность та лии [22]; M. Sergi и со ав то ры (1999) счи та ют бо лее ин фор матив ным от но ше ние объ е ма та лии к объ е му бе дер (ОТ/ОБ) [26]. Пред по ла га ет ся, что аб до ми наль ный тип ожи ре ния спо соб ст ву ет раз ви тию об ст рук тив ных ап ноэ за счёт сни же ния лё гоч ных ды ха тель ных объ ёмов, что при во дит, с од ной сто ро ны, к хро ни че с кой ги по ксе мии и на ру ше нию хе мо ре цеп тор ной чув ст витель но с ти, с дру гой -к на ру ше нию ре флек тор ной акти ва ции мышц ВДП во вре мя ды ха тель но го цик ла.…”
Section: мг полуэктовunclassified